Advances in the role of the IGF signaling system in myelodysplastic syndromes and acute myeloid leukemia - Wang, Yifan; Dong, Xinyu; Tao, Shandong; Chen, Qiuni; Chen, Yue; Zhang, Lijuan; Shi, Yuye; He, Zhengmei; Yu, Liang; Wang, Chunling (Frontiers in Oncology, 2025)
The insulin-like growth factor (IGF) signaling system comprises functionally specific ligands (IGF-I and IGF-II), receptor (IR), and binding proteins (IGFBP). IGFs are activated by binding to their receptor, IGF-IR, which is a tyrosine kinase receptor. This activation initiates signaling cascades such as PI3K/Akt and MAPK/ErK pathways, which are essential for cell proliferation, differentiation, and survival. Growing evidence links the IGF system to various hematological disorders, yet comprehensive reviews on its role in Myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) are limited. To advance understanding in this area, we aim to summarize the emerging evidence on the involvement of IGF signaling in the pathogenesis of MDS and AML. Specifically, we highlight how dysregulation of IGF-I, IGF-IR, and IGFBPs contributes to disease progression, encompassing clonal hematopoietic abnormalities, ineffective hematopoiesis in MDS, and the development of AML. The potential therapeutic implications of targeting the IGF signaling pathway, including the role of NVP-AEW541 and NVP-ADW742 effectively suppressing AML cell proliferation and enhancing chemotherapy sensitivity, are also explored. By integrating current findings, this review provides novel insights into the mechanistic role of IGF signaling in MDS and AML and its therapeutic implications, thereby guiding future research and potential clinical applications. Given the challenges, such as pathway redundancy and therapy resistance, further investigations are necessary to validate IGF-targeted therapies and optimize their clinical utility in hematologic malignancies.